Harga, Kualitas dan Promosi terhadap Tingkat Kepuasan Pelanggan dalam Pembelian Produk Handphone di PT. Christaraka Sukses Selalu Kota Medan - Shanweda Napitupulu, Cristine; Friciliya Hasugian, Silvi; Rocky Purba, Jhon; Faisal Mirza, Deni (IPM2KPE, 2024)
This study aims to analyze the effect of price, quality, and promotion on customer satisfaction at PT Christaraka Sukses Selalu, Medan City. The research method used is a quantitative approach, with data collected from 85 consumers using the Slovin technique to determine the sample. Based on the t-test, price and quality do not have a significant effect on customer satisfaction, with a t-count value smaller than t-table and a significance above 0.05. On the other hand, promotion has a significant effect, with a t-count greater than t-table and a significance of 0.001. The simultaneous F test shows that price, quality, and promotion together have a significant effect on customer satisfaction, with a calculated F value of 53.606 and a significance of 0.001. The Adjusted R Square value of 0.598 indicates that 59.8% of the variation in customer satisfaction can be explained by the variables of price, quality, and promotion, while the remaining 40.2% is influenced by other factors not examined in this study. Keywords: Price, Quality, Customer Satisfaction, Promotion